APPLICATION OF PROGRESSIVE MOBILIZATION TO FUNCTIONAL STATUS AND MUSCLE STRENGTH IN POST SECTIO PATIENTS WITH ECLAPMSIA IN THE ICU ROOM OF RADEN MATTAHER HOSPITAL - Syarbaini Syarbaini; Isra' Noval Girianda (Lembaga Pengembangan Kinerja Dosen, 2023)
Patients with Sectio Caesarea in some cases have worsened so they have to be rushed to the ICU to get intensive care. This case study aims to obtain an overview of the application of progressive mobilization to improve functional status and muscle strength in post-sectio patients with eclampsia in the ICU. This case study uses a descriptive design. The application of progressive mobilization performed on patients has been successfully implemented up to level 3. The results of this case study found that progressive mobilization can increase muscle strength from 0 to 56 and functional status from 0 to 65, and can reduce the risk of ICU-AW, speed up the length of release ventilator. Progressive mobilization is effective in increasing muscle strength, and functional status, and can improve the improvement of hemodynamic status and oxygenation status, and prevent the occurrence of ICU-AW. Progressive mobilization can be implemented immediately to shorten the length of stay in the ICU.